Does high inflation cause central bankers to lose their job? Evidence based on a new data set - Axel Dreher; Jan-Egbert Sturm; Jakob de Haan (ETH Zurich, KOF Swiss Economic Institute, 2007)
This paper introduces new data on the term in office of central bank governors in 137 countries for 1970-2004. Our panel models show that the probability that a central bank governor is replaced in a particular year is positively related to the share of the term in office elapsed, political and regime instability, the occurrence of elections, and inflation. The latter result suggests that the turnover rate of central bank governors (TOR) is a poor indicator of central bank independence. This is confirmed in models for cross-section inflation in which TOR becomes insignificant once its endogeneity is taken into account.
Keywords: E5; 330; central bank governors; central bank independence; inflation; Zentralbank; Führungskräfte; Arbeitsmobilität; Zentralbankautonomie; Inflation; Schätzung; Welt